The Effect of Tourist Visits, Length of Stay, ROR and Number of Restaurants on Regional Original Income in Bali Province - Putra, Arvaro Oktaviano Murbawanto; Dewi, Made Heny Urmila (Peneliti.net, 2025)
The Covid-19 pandemic produced an economic slowdown in Indonesia, especially Bali Province, as seen by a decrease in Regional Original Income for cities/regencies in Bali Province during and after the pandemic. The tourism sector needs to be reviewed for its potential and strength in collecting regional income, This study which includes 108 observations, attempts to examine how the number of tourist visits, length of stay, hotel room occupancy rate (TPK) and number of restaurants, affect original reional income in Bali Province between 2010 and 2021, This study uses panel data for for multiple regression analysis, which is then analyzed with E-Views 10. The outcomes clarify that tourist visits, length of stay, TPK and number of restaurants together have a noteworthy impact on original regional income of Bali regencies/cities in 2010-2021. Tourist visits and TPK have a positive and in part noteworthy impact ect on the original regional income of Bali regencies/cities in 2010-2021. Length of Stay and Number of Restaurants do not partially influence the original regional income of Bali regencies/cities. Promotion and development of post-pandemic tourism needs to be intensified and maximize the source of Regional Original Income for regencies and cities in Bali because of the Covid-19 pandemic.